Understanding oral cancer disparities in India: Exploring socioeconomic and demographic factors impacting access to care and outcomes - Amol S. Dhane (Oral Oncology Reports)
The high prevalence rates, inequalities in treatment outcomes and access to care and other factors make oral cancer a major public health concern in India. The diverse aspects of oral cancer disparities in India are examined in this article, with a particular emphasis on the socioeconomic and demographic variables that affect outcomes and access to care. Disparities still exist even with improvements in treatment modalities. These are caused by low socioeconomic position, low health literacy, cultural customs, and gender variations in risk behaviors. A comprehensive strategy that includes investments in healthcare infrastructure, health education programs, and tobacco control measures is needed to reduce the disparities in oral cancer. India may strive toward providing equal access to oral cancer care for all its population by eliminating systemic injustices and encouraging preventative measures.